Risk factors of admission in school children with severe atopic dermatitis. Issue 1 (18th October 2022) - Miyaji, Yumiko; Yamamoto‐Hanada, Kiwako; Fukuie, Tatsuki; Narita, Masami; Ohya, Yukihiro
Abstract: There are no data about risk factor of admission and long‐term (>1 year) prognosis of proactive therapy using topical corticosteroids (TCSs) in school children. This study aims to identify the prognosis of school children over 3 years treated with proactive therapy after hospitalization due to atopic dermatitis (AD). This retrospective cohort study used electronic medical record data of schoolchildren (aged 5–19 years) with a long‐term admission program for AD at the National Center for Child Health and Development from January 2008 to December 2013. Long‐term prognosis at 1 and 3 years after discharge were retrospectively identified from their medical records. The most common exacerbation factor was poor adherence (51.8%). At 1 and 3 years after hospitalization, 87.3% and 74.3%, respectively, of the children used TCSs on their trunk and limbs less than twice a week. Investigator's Global Assessment of AD scores were ≤1 for 81.0%and 75.7% at 1 and 3 years after discharge, respectively. AD was well‐controlled during follow‐up. Rehospitalization due to AD was observed in 11.8% children. Poor adherence was biggest risk factor for admission. Children with severe AD could achieve well‐controlled AD with a long‐term admission AD program and home‐based proactive therapy using TCSs for 3 years after discharge. Maintaining good adherence for AD treatment is required to prevent exacerbation and improve future prognosis in school children. However, we need to engage for the children who required rehospitalization.